2020
DOI: 10.1016/j.str.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The Polyglutamine Expansion at the N-Terminal of Huntingtin Protein Modulates the Dynamic Configuration and Phosphorylation of the C-Terminal HEAT Domain

Abstract: Highlights d The cryo-EM analysis on normal (Q23) and disease (Q78) HTT are described d The polyQ expansion alters the relative movement of HTT domains d The polyQ expansion at N terminus alters the global phosphorylation pattern of HTT d Ser2116 phosphorylation affects the global structure and function of HTT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 75 publications
3
37
0
Order By: Relevance
“…As reported by Guo and colleagues 20 , we were also unable to express recombinant HAP40 alone, although it is readily expressed in the presence of HTT, a trend that parallels our in vivo observations. In the absence of HAP40, we and others have shown that recombinant HTT self-associates and is conformationally heterogenous in vitro 21,22,34 . Cryo-EM analysis of our apo HTT samples yielded a 12 Å resolution envelope (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…As reported by Guo and colleagues 20 , we were also unable to express recombinant HAP40 alone, although it is readily expressed in the presence of HTT, a trend that parallels our in vivo observations. In the absence of HAP40, we and others have shown that recombinant HTT self-associates and is conformationally heterogenous in vitro 21,22,34 . Cryo-EM analysis of our apo HTT samples yielded a 12 Å resolution envelope (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 78%
“…Biophysical and biochemical analyses comparing purified HTT and HTT-HAP40 samples have revealed that HAP40-bound forms of HTT exhibit reduced aggregation propensity, greater stability and monodispersity as well as conformational homogeneity 20,21 . Consequently, apo HTT is a more difficult sample to work with for structural and biophysical characterisation, and several studies to date have required cross-linking approaches to constrain the HTT molecule to facilitate its analysis, suggesting HTT-HAP40 interactions may stabilize HTT 22,23 . The biological function of the HTT-HAP40 complex however, remains elusive, and it is not clear if the function of this complex differs from apo HTT in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, polyQ expansion does not result in an abrupt conformational change of the HTT N-terminus (Bravo-Arredondo et al, 2018; Newcombe et al, 2018; Warner et al, 2017). A recent study showed cryo-EM analyses at ∼10 Å resolution of recombinant 23QHTT and 78QHTT upon GraFix stabilization, in combination with XL-MS, small-angle X-ray scattering and hydrogen-deuterium exchange (Jung et al, 2020). This study indicated that apo HTT (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Apo HTT, i.e. not bound to HAP40, may be more flexible and undergo subtle conformational changes upon polyQ expansion (Jung et al, 2020). Whether such rearrangements are related to the described loss-or gain-of-function phenotypes of mutant full length HTT in HD (Cisbani and Cicchetti, 2012; Zuccato et al, 2010) requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation